Research on the Modulation Performance in GPON System - Li Li; Chen Yan-Tao; Zhang Ji-Jun; Li Zhi-Rui; Cheng Wan-Li (Institute of Advanced Engineering and Science, 2014)
This paper mainly does research and analysis on anti-dispersive performance and anti-nonlinear performance for intensity modulation formats such as NRZ, RZ, CS-RZ, DRZ, MD-RZ in 40Gbps high-speed single-channel optical transmission system. It compares the five pattern modulation formats in dispersion tolerance, nonlinear tolerance, and advantages and disadvantages in transmission distance. Anti-nonlinear effect ability of CSRZ, RZ are stronger than that of NRZ code; in the single-channel transmission system, DRZ and improved modulation format MDRZ have better resistance foranti-nonlinear performance, so they are suitable for long-distance transmission. RZ has the minimum dispersion tolerance. NRZ than RZ has higher spectrum efficiency than RZ, and thus have a better dispersion tolerance. CSRZ code has higher spectral efficiency, higher dispersion tolerance and nonlinear tolerance than RZ code, making it more suitable for long distance transmission.